Genetic structure of the “Gaviluud” Mongolian sheep population (Proceedings of the Institute of Biology, 2022)
The genetic structure of the “Gaviluud” sheep population of Khanbogd Soum, Umnugovi Province was studied by polymorphism of the multilocus DNA AG-ISSR marker. A total of 24 fragments of the AG-ISSR-DNA marker were discovered in the study, and 83.33% of them were polymorphic. The genetic makeup of the “Gaviluud” sheep population, as revealed by polymorphism of the AG-ISSR-DNA marker, differed significantly from that of the “Saintsagaan” and “Darkhad” sheep populations.“Гавилууд” хонины сүргийн генетик тогтоцӨмнөговь аймгийн Ханбогд сумын “Гавилууд” хонины популяцийн генетик тогтцыг мултилокусын ДНХ-ийн AG-ISSR маркерын полиморфизмоор төлөөлүүлэн судлав. “Гавилууд” хонины популяцид AG-ISSR-DNA маркерын полиморфизмыг судлахад AG-ISSR-DNA маркерын 24 фрагмент тохиолдож байгаа ба AG-ISSR маркерын 83.33% нь полиморф байгааг илрүүлэв. “Гавилууд” хонины популяцийн AG-ISSR-DNA маркерын полиморфизмоор илэрхийлсэн генетик тогтоц “Сайнцагаан” болон “Дархад” үүлдрийн хониныхоос статистикийн хувьд бодитойгоор ялгаатай байв.Түлхүүр үгс: Монгол хонь, популяцийн генетик тогтоц, ДНХ-ISSR маркер, ДНХ-полиморфизм